Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To evaluate the expression \( -4|5 + m| \) for \( m = -3 \), follow these steps:
1. Substitute \( m = -3 \) into the expression:
[tex]\[ -4|5 + (-3)| \][/tex]
2. Simplify inside the absolute value:
[tex]\[ 5 + (-3) = 5 - 3 = 2 \][/tex]
3. Find the absolute value of 2:
[tex]\[ |2| = 2 \][/tex]
4. Multiply by -4:
[tex]\[ -4 \times 2 = -8 \][/tex]
Therefore, the value of the expression is [tex]\( -8 \)[/tex].
1. Substitute \( m = -3 \) into the expression:
[tex]\[ -4|5 + (-3)| \][/tex]
2. Simplify inside the absolute value:
[tex]\[ 5 + (-3) = 5 - 3 = 2 \][/tex]
3. Find the absolute value of 2:
[tex]\[ |2| = 2 \][/tex]
4. Multiply by -4:
[tex]\[ -4 \times 2 = -8 \][/tex]
Therefore, the value of the expression is [tex]\( -8 \)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.